2017
DOI: 10.1111/eufm.12123
|View full text |Cite
|
Sign up to set email alerts
|

Do Managerial Practices Matter in Innovation and Firm Performance Relations? New Evidence from the UK

Abstract: The innovation and firm performance relationship remains a puzzle, as all types of innovation are not equally beneficial. Besides, better‐managed firms can perform better. Integrating these two strands of literature, we examine whether managerial practices explain this relationship using data from UK firms during 1992–2014. We find that firms which focus on R&D activities jointly with better managerial practices benefit favourably. During the post‐crisis period, higher intangibles are only beneficial when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 73 publications
7
54
0
1
Order By: Relevance
“…Second, instead of taking R&D investment as an expense, we construct the R&D intensity to conduct another robustness check, which is the total amount of investment in R&D divided by total sales (both in RMB). It shows the contribution of R&D per unit of output (Nemlioglu and Mallick, 2017; and is helpful to avoid selection bias caused by zeros (Egger et al, 2019). The 2SLS estimation results are shown in Panel B of Tables 7 and 8, confirming our earlier results.…”
Section: Randd Intensitysupporting
confidence: 86%
“…Second, instead of taking R&D investment as an expense, we construct the R&D intensity to conduct another robustness check, which is the total amount of investment in R&D divided by total sales (both in RMB). It shows the contribution of R&D per unit of output (Nemlioglu and Mallick, 2017; and is helpful to avoid selection bias caused by zeros (Egger et al, 2019). The 2SLS estimation results are shown in Panel B of Tables 7 and 8, confirming our earlier results.…”
Section: Randd Intensitysupporting
confidence: 86%
“…Though Schumpeter has introduced several types of innovation; product, market, process and organization etc. Not all the innovations are equally useful; some innovations (characterized by top management practices) are more beneficial for a firm's profitability because of R & D activities and innovative tactics [18]. In addition, it is also suggested that MI enables business firms to adopt various innovative and technological processes that are required for smooth running to operational activities [48].…”
Section: Management Innovation and Organization Performancementioning
confidence: 99%
“…Recent studies claim that innovation is the best choice for organizations to survive a long run in turbulent markets [17]. A variety of innovation types have been discussed such as eco-innovation, social innovation, product innovation, marketing innovation and organization innovation [18] that can impact a firm's performance. Out of all the innovations, the MI (e.g., [18]) and TI ( [19]) have been considered the most prominent factors for the survival of organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further historical development, it has been recognised that the conditions of resource utilisation to achieve a competitive advantage can be met by intangible assets that are sourced by people and their capabilities, which, at the same time, must be crucial to achieving strategic goals [31]. Each person is an original and unrepeatable individual and thus becomes a rare and valuable resource, which, moreover, is able to achieve originality in problem solving by its creativity and, thus, is the main source for achieving a competitive advantage [32].…”
Section: Impact Of Age Management On Competitive Advantagementioning
confidence: 99%